Disease outcomes and nodal recurrence in patients with papillary thyroid cancer and lateral neck nodal metastases. Issue 4 (14th January 2013) - O'Neill, Christine J.; Coorough, Nicholas; Lee, James C.; Clements, Joshua; Delbridge, Leigh W.; Sippel, Rebecca; Sywak, Mark S.; Chen, Herb; Sidhu, Stan B.
Abstract Background The prognostic influence of lateral neck nodal metastases present at the time of diagnosis of papillary thyroid cancer (PTC) remains controversial. This study aims to document disease outcomes and nodal recurrence rates in such patients. Methods Patients with PTC and lateral neck nodal metastases who underwent concurrent total thyroidectomy, central and lateral compartment neck dissection between 2000 and 2010 were identified from the prospectively maintained surgical databases of The University of Sydney and University of Wisconsin Endocrine Surgical Units. Disease outcomes and nodal recurrence rates were compared at 12 months post‐operatively and in longer‐term follow‐up. Results During this 11‐year period, 121 patients were identified. Mean age was 45 years; 58% were female and 98% underwent post‐operative radioactive iodine ablation. At a median follow‐up of 31 months (range 12–140), there were no disease‐specific deaths and disease‐free survival (defined by stimulated serum thyroglobulin (Tg) < 2.0 μg/L, negative clinical and radiological examination) was 66%. Of the 50 patients with persistently elevated Tg measured 12 months post‐operatively, 15 developed clinical lateral neck nodal recurrence. All have undergone re‐operative surgery. Elevated stimulated Tg at 12 months post‐operatively and a nodal ratio of >30% were significantly associated with an increased risk of lateral neck nodal recurrence. Conclusion With total thyroidectomy, formal compartmental neck dissection and radioactive iodine treatment, disease‐free survival can be achieved in the majority of patients with PTC and synchronous lateral neck nodal metastases. A persistently elevated Tg post‐operatively and a high ratio of metastatic nodes identify patients at increased risk of locoregional recurrence.